Aspergillosis complicating a microwave ablation cavity. (13th September 2016) - Singh, Saurabh; Bandula, Steven; Brown, Jeremy; Whelan, Jeremy; Illing, Rowland
Abstract : We present a case of a patient who following chemotherapy developed semi-invasive pulmonary aspergillosis and an aspergilloma in a lung cavity previously formed by microwave ablation (MWA). A 55-year-old woman presented with cough and shortness of breath after finishing three cycles of chemotherapy for a metastatic nerve sheath tumour. She had been treated by MWA for pulmonary metastases 2 years previously which resulted in a residual right apical lung cavity. Postchemotherapy imaging showed that this cavity had enlarged, developed a thicker wall and contained lobulated soft tissue with a crescent sign on coronal reformats. In addition, the patient's Aspergillus -specific IgG was markedly raised. Treatment with itraconazole improved the symptoms and reduced the cavity size and wall thickness. This case shows that persisting lung cavities after MWA are a potential site for semi-invasive aspergillosis and has implications for the timing of chemotherapy in patient with metastatic lung disease.